Dog Man : Fetch-22 - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (New York, NY : Graphix, an imprint of Scholastic, 2019)
"Petey the Cat is out of jail, and he has a brand-new lease on life. While Petey's reevaluated what matters most, Li'l Petey is struggling to find the good in the world. Can Petey and Dog Man stop fighting like cats and dogs long enough to put their paws together and work as a team? They need each other now more than ever, Li'l Petey--and the world--is counting on them!"--OCLC.
2.7
3-6.
3-6
Keywords: Cats -- Comic books, strips, etc -- Juvenile fiction; Dogs -- Comic books, strips, etc -- Juvenile fiction; Humorous stories; Police -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cats -- Fiction; Dogs -- Fiction; Humorous stories; Police -- Fiction; Cats -- Comic books, strips, etc -- Fiction; Dogs -- Comic books, strips, etc -- Fiction; Humorous graphic novels; Police -- Comic books, strips, etc -- Fiction; Graphic novels; Humorous comics